The Balance Recovery Mechanism Following a Sudden External Anterior- Posterior Perturbation in Individuals with Kyphosis - Mehrdad Anbarian; parviz Zareie; ali Yalfani; masoud Mokhtari (Sport Sciences and Health Research)
The purpose of this study was to determine the balance recovery mechanism following a sudden external perturbation in kyphotic individuals in comparison with normal individuals (control). For this purpose, ten males (mean age: 21.5+1.6 years) with increased thoracic kyphosis>40 degrees and 15 individuals (mean age: 22.1+1.19) without thoracic kyphosis (control) were selected to participate in the study. Six reflective markers were attached to the right side of the acromion, greater trochanter, lateral femoral epicondyle, external malleolus, calcaneus and fifth metatarsal and a 4-segment 2-dimension model was defined. Kinematic data were collected using three high-speed cameras at 120 Hz. Each subject conducted six 5-second trials including three quite standing trials and three unexpected anterior-posterior perturbed trials triggered by a weight equivalent to 10% of the subjects’ body weight. The change in range of motion and torque deviation of the hip, knee and ankle joints were calculated with Eva software. Statistical data were analyzed by analysis of variance with repeated measures (p=0.05). The results showed that kyphotic subjects had a greater significant change and deviation in their range of motion after perturbation in their hip (p=0.000) and ankle (p=0.000) joints compared with control subjects. There was a relative similarity in joint torque deviation pattern in response to a balance perturbation between the two groups. But this torque deviation fluctuated with greater amplitude in kyphotic group. These findings illustrated that postural 1 - Corresponding – Author : Tel : 09188152907 , Email : m_anbarian@yahoo.com Journal of Faculty of 13 Physical Education, University of Tehran strategy and responses employed by kyphotic individuals to recover upright posture following forward balance perturbation is different from those in control group. Consequently, kyphosis can influence postural reaction strategy in response to a balance perturbation.